PENGARUH LATIHAN KNEE-TUCK JUMP TERHADAP POWER OTOT TUNGKAI PADA TIM BOLAVOLI PUTRA MADRASAH ALIYAH AL-HIDAYAH BANTAN KABUPATEN BENGKALIS - M. Arif Rahman; Ramadi Ramadi; Ni Putu Nita Wijayanti (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The problem in this research is when a player or a smasher is practicing a smash with a smash technique that is incorrect but there are a lot of balls that concern the net. The title in this study is